Effects of clinical use of NiTi reciprocating instruments on cyclic and torsional resistance, and on roughness - Edson Jorge Lima MOREIRA; Henrique dos Santos ANTUNES; Victor Talarico Leal VIEIRA; Daniele Moreira CAVALCANTE; Henrique Eduardo OLIVEIRA; Diogo da Silva OLIVEIRA; Gustavo DE-DEUS; Emmanuel João Nogueira Leal da SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstrac The aim of the present study was to evaluate the cyclic fatigue, torsional resistance and surface roughness of Reciproc R25 instruments in four different situations, namely as new instruments and as instruments tested after clinical preparation of one, two or three maxillary molars with four root canals. The total time required to perform each root canal preparation was recorded. Cyclic fatigue resistance was determined by the time to fracture using a customized testing device (n = 10 per group). The torsional test evaluated the torque and angle of rotation to failure according to ISO 3630-1 (n = 10 per group). The roughness of the working parts of new and used instruments was evaluated with a profilometer (n = 5 per group). Statistical analysis was performed using one-way ANOVA and Tukey's test. The level of significance was set at 5%. No fractures or deformations were observed after clinical use. Higher preparation time was needed during the third use of the instruments for all root canals (p < 0.05). There were no significant differences among the groups in regard to either cyclic fatigue or torsional resistance (p > 0.05). Regarding the roughness measurements, groove depth was higher on new and one- versus two- or three-maxillary-molar-prepared instruments (p < 0.05). It can be concluded that the clinical use of Reciproc instruments increased preparation time and decreased surface roughness. However, clinical use did not affect the cyclic fatigue or torsional resistance of the Reciproc instruments.